Criminal circumstance : a dynamic multi-contextual criminal opportunity theory /: a dynamic multi-contextual criminal opportunity theory. ([2018?]) - Wilcox, Pamela, 1968-; Land, Kenneth C; Hunt, Scott A, 1960-
No abstract available